2020
DOI: 10.1177/0954405420911310
|View full text |Cite
|
Sign up to set email alerts
|

Machine tool movement control method combining the benefit of software and real-time interpolator for sculpture surface machining

Abstract: In the traditional sculpture surface machining process, the G01 code is still the mainstream trajectory. Furthermore, real-time feedrate scheduling and corner smooth algorithm in controller constitute the mainstream method to improve the machining process of short line G01 code in sculpture surface machining. However, the G01 code’s discontinuity and the limits of real-time calculation capacity hinder the use of high-speed machine tools and the accuracy of the machined part. In this article, a new method for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The study found that the application satisfaction of micro-nano technology in sculpture can reach above 8. Lu et al [8] has also found that the traditional sculpture design method has the defects of discontinuity and poor real-time computing power. It uses computeraided technology and real-time controller to realize a new type of sculpture design technology.…”
Section: Related Studiesmentioning
confidence: 99%
“…The study found that the application satisfaction of micro-nano technology in sculpture can reach above 8. Lu et al [8] has also found that the traditional sculpture design method has the defects of discontinuity and poor real-time computing power. It uses computeraided technology and real-time controller to realize a new type of sculpture design technology.…”
Section: Related Studiesmentioning
confidence: 99%
“…Mou and Gao 17 proposed a reliable process planning method based on fuzzy comprehensive evaluation via historical machining data. Lu et al 18 proposed a new method to transfer the real-time data of machine tool to the computer-aided manufacturing software so as to release the resources of machine controller. These researchers provide different solutions for different applications, which is not enough to improve the intelligence of machine tools.…”
Section: Related Workmentioning
confidence: 99%
“…1 In the machining process, because the corner of G01 tool path is only continuous position (C 0 ), and the discontinuity in tangential and normal directions will lead to the fluctuation of acceleration and jerk of each axis of the machine tool, which will cause tool vibration, destroy the surface smoothness of the parts and reduce the machining quality. [2][3][4] In order to improve the machining efficiency and quality of G01 tool path, experts and scholars have carried out in-depth research on corner smoothing and interpolation technology. [5][6][7] That is, the high-order spline curve is used to interpolate the corner to generate a smooth tool path, and then the corresponding acceleration and deceleration(ACC/DEC) control method is selected for velocity planning and interpolation, which provides interpolation instructions for the position controller of the CNC system to achieve smooth and continuous feed motion.…”
Section: Introductionmentioning
confidence: 99%
“…Although the calculation efficiency is improved to a certain extent, the C 2 continuous path after smoothing can only ensure continuous motion of tool axis acceleration. Compared with the continuous trajectory of C 3 , the continuous trajectory of C 2 has large fluctuation in the jerk during the operation of the machine tool. 24 The discontinuity and high fluctuation of the jerk curve will lead to the unstable motion of the machine tool and affect the machining quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation